A Deixis Analysis Song Lyric of “ Reckless” By Madison Beer - Elvina Rosa Dilla; Foury Widya Anjani; Indahh Rustiyani; Syafa Salsabila Putri Annazmi; Emeliya Sukma Dara D (The Doctoral Studies Program of Linguistics of Udayana University, 2023)
This study aim of the research is to identify the type ofdeixis and the dominant type of deixis in the lyrics ofMadison Beer's song Reckless. This study is a type ofqualitative research. Data collection techniques includelistening to songs and analyzing Madison Beer's song